Genetic Profile of Local Buffalo (Bubalus bubalis) Populations in Pacitan and Tuban, East Java, Indonesia Measured by the Molecular Marker of INRA032 Locus - Rahmawati, Laily Isnaini; Basith, Abdul; Lestari, Fitria (Universitas Negeri Surabaya, 2023)
This study focused on the application of microsatellite markers at the INRA032 locus for genetic diversity assessment in buffalo (Bubalus bubalis) populations in Pacitan and Tuban Regencies, East Java, Indonesia. The total number of samples used was 16, each population represented by 8 samples. Genetic diversity assessment parameters include allele frequency, the Polymorphism Information Content (PIC) and heterozygosity. The results showed that based on the INRA032 locus, the Tuban buffalo population had a higher allele frequency range (0.08 to 0.33) than the Pacitan population (0.18 to 0.31). The average PIC value in both populations was 0.39, so it can be concluded that the INRA032 locus is informative enough to detect polymorphisms in both populations. The percentage heterozygosity of the Pacitan buffalo population is 88%, which is higher than the Tuban population at 50%, suggesting that the genetic diversity of the two populations is still quite high despite the decreasing trend in population numbers.